Foils and Diamonds: Using Material Culture, Reviews, and Prefaces to reappraise the Minerva Press - Davies, Colette (Romanticism on the Net)

(untitled) (Université de Montréal, 2021)
This article provides a targeted exploration of how one Minerva Press author, Eliza Parsons, engaged with Romantic era discourses about imitation and originality in literature through the paradigm of jewellery. It investigates how specific materials, jewels and foils, were perceived in wider Romantic culture and highlights the incongruencies between the literary critics’, authors’, and wider society’s responses to them. By placing Parsons’ prefaces in dialogue with commentaries on imitation, originality and aesthetic paradigms by Edward Young, Mary Wollstonecraft, and others, this article argues that the jewellery analogy afforded Parsons the opportunity to intervene in the era’s denigrating ideologies about the value of imitation in novels. It reads Parsons’ analogy comparing her work to foil in the preface of Ellen and Julia (1793) as a strategy which proposes that imitation does not preclude literary or commercial or cultural value. This paradigm indicates that imitative works are valuable for their wide appeal and for how they innovate upon tropes they imitate. The article concludes by suggesting that the jewellery and foil analogy posits that all works may originate from imitation to differing extents, just as diamonds can be made from foil.